When the Maltese army conquered Djerba in 1039 - Mercieca, Simon; Cassar, Frans X. (The Malta Independant, 2016)
Keywords: Invasions chrétiennes – Djerba; Relations – Djerba – Malte

Old and new enemies (1420-1433): The difficulties of organizing a Royal fleet against the Tunisian island of Djerba - Molins, Pol Junyent (2016)
The reign of Alphonso the Magnanimous (1416-1458) is an exceptional laboratory for the study of war. Its recurrence and the different areas where the armies were mobilized are a unique setting for observation. It is even more outstanding thanks to the vast amount of documentation preserved, which allows us to study the period in a much wider way. The aim of this paper is to do a first approximation to the great effort done by the monarchy of the Crown of Aragon to end the old military conflicts ―war against Genoa and Sardinia (1420-1421) and the problems with the crown of Castile since 1425― before starting the North African offense. We will especially focus on the open war against Castile (1429-1430), a conflict contrary to the intentions of the king, who claimed to his aristocracy not to fall into Castilian provocations. In addition, the king encountered great difficulties in his own territories, since the projects of the leaders of the Catalan Courts clashed against the eagerness of the king. Therefore, since 1423 this sequence of conflicts impeded the departure of a royal fleet against the Tunisian island of Djerba that was started to build in 1429, but was not materialized until 1432. Finally, we will display the genesis of the military conflicts of Alphonso the Magnanimous to understand how the eagerness of the king brought him to reach agreements with his old enemies and shift his alliances. The king’s necessity of resources for building new armies and, thus, creating new enemies is, in this sense, the result of the expansionist desire of the monarch.
Swedish History Museum
Keywords: Invasions chrétiennes – Djerba

"Als calafats e mestres d’axe e altres qui obrat e lavorat han". Construcción naval en torno a la armada de Alfonso el Magnánimo contra la isla de Gerba (1430-1432) - Molins, Pol Junyent (2016)
En las atarazanas reales de Barcelona se trabajaba en la reparación y construcción de navíos y galeras. Uno de los momentos más importantes de su existencia era la preparación de una flota destinada a una empresa concreta. La voluntad de esta comunicación es la de reconstruir los aspectos asociados a la construcción naval centrándonos en la obtención, compra y transporte de la madera de los a la capital catalana, para luego poder ver los procesos de su manipulación y preparación, dónde intervienen multitud de oficios.
Keywords: Invasions chrétiennes – Djerba

السياسة الصليبية الإسبانية تجاه بلاد المغرب بُعَيد سقوط غرناطة (1492-1504م/897-910هـ) - قبج, عامر أحمد (مجلة جامعة القدس المفتوحة للبحوث الإنسانية والاجتماعية, 2016)
مثّلت السياسة الإسبانية تجاه بلاد المغرب الإسلامي حلقة مهمة من حلقات الحروب الصليبية المتأخرة، ورغم عودة جذور الأطماع الإسبانية في بلاد المغرب إلى عهود مبكرة من تاريخ الصراع الإسلامي المسيحي؛ إلا أنها قويت بعد ضعف الدولة الموحدية وانهيارها في كل من الأندلس والمغرب منذ القرن الثالث عشر الميلادي/السابع الهجري.وبلغت السياسة العدائية ذروتها؛ عندما تمكّن الإسبان من إنهاء الحكم الإسلامي في الأندلس بُعَيد سقوط غرناطة؛ آخر المعاقل الإسلامية عام 1492م، وحينها أصبح الطريق ممهّداً لنقل الصراع إلى بلاد المغرب، برعاية بابوية، وبتوجيه وتنفيذ مباشر من المؤسسة الدينية والسياسية الإسبانية على حد سواء، لتحقيق أهداف استعمارية وتنصيرية ، وسياسية ، واقتصادية، فسيطر الإسبان على بلدتي مليلة وغساسة، واتخذوا منهما موطئ قدم للسيطرة على باقي المناطق الساحلية، فمثلت السيطرة عليهما باكورة الإنجازات الاستعمارية الإسبانية في بلاد المغرب خلال القرن السادس عشر.
Keywords: Invasions chrétiennes – Djerba